2007
DOI: 10.1161/01.str.0000257995.74834.92
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the Stable Carotid Plaque

Abstract: Background and Purpose-Calcification has been associated with carotid plaque stability; however, an acceptable in vivo method to define plaques based on this component remains to be developed. The purpose of our study was to compare calcified and noncalcified volumes of carotid artery culprit symptomatic plaques with asymptomatic plaques using multidetector computed tomography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(48 citation statements)
references
References 37 publications
2
46
0
Order By: Relevance
“…Previous studies33, 41, 42 measuring CPV by both MRI and CT suggested that CPV was associated with cardiovascular risk factors and symptoms of cerebral ischaemia. If the accuracy of tUS measurement of CPV is confirmed in larger studies, it is possible that the measurement of CPV could replace severity of stenosis as the principal indication for CEA.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies33, 41, 42 measuring CPV by both MRI and CT suggested that CPV was associated with cardiovascular risk factors and symptoms of cerebral ischaemia. If the accuracy of tUS measurement of CPV is confirmed in larger studies, it is possible that the measurement of CPV could replace severity of stenosis as the principal indication for CEA.…”
Section: Discussionmentioning
confidence: 96%
“…13,[26][27][28][29][30] In a recent study on MDCT, the relationship between stroke symptoms and plaque morphology was assessed. 30 In the study, expansive carotid remodeling was greater in patients with cerebral ischemic symptoms than in asymptomatic patients, though there was no significant difference in the plaque eccentricity between symptomatic and asymptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…14 The CTA modality with modern, multislice scanners is excellent for localization and quantification of calcification, 21 and the relationship to internal architecture, ulceration, and prediction of "vulnerability" is becoming clear. 13,29,30 Although the CT calcification grade is known to predict the expansion of coronary stents 15 and has been suggested to be a relative contraindication to CAS, 8,16 few investigators use plaque morphology to help guide the choice of treatment 19 or to predict the immediate or long-term morphological success of CAS procedures.…”
Section: Discussionmentioning
confidence: 99%